2010
DOI: 10.1103/physreve.81.011605
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic scaling study of vapor deposition polymerization: A Monte Carlo approach

Abstract: The morphological scaling properties of linear polymer films grown by vapor deposition polymerization are studied by 1+1D Monte Carlo simulations. The model implements the basic processes of random angle ballistic deposition (F) , free-monomer diffusion (D) and monomer adsorption along with the dynamical processes of polymer chain initiation, extension, and merger. The ratio G=D/F is found to have a strong influence on the polymer film morphology. Spatial and temporal behavior of kinetic roughening has been ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Monte Carlo (MC) models are widely used for the simulation of the growth of thin films 27–29, and the one we use in this paper has already been successfully applied in many cases 16, 17, 19. It considers the deposition of effective particles on a cubic three‐dimensional N L × N L × N H grid, each cell representing a spatial volume of Δ 3 , with periodic boundary conditions, whose cells may take the values 0 (empty cell), or 1 (a deposited particle occupies the cell).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Monte Carlo (MC) models are widely used for the simulation of the growth of thin films 27–29, and the one we use in this paper has already been successfully applied in many cases 16, 17, 19. It considers the deposition of effective particles on a cubic three‐dimensional N L × N L × N H grid, each cell representing a spatial volume of Δ 3 , with periodic boundary conditions, whose cells may take the values 0 (empty cell), or 1 (a deposited particle occupies the cell).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…A 1 + 1D lattice model similar to the one employed earlier [15,17,18] was used in our study of polymer chain aggregates. In our computational model, a number of Monte Carlo moves were employed to simulate various dynamical processes occurring during the VDP growth.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Although vapor transfer [11][12][13][14] is a popular method used to grow organic nanostructures, literature on the size controllable growth of the nanostructures is very limited. Many recent studies [15][16][17][18][19] have focused on the behavior of overall polymer films properties like film density, interface width, end-to-end distance, etc. However, there is a very limited understanding of the aggregation process of polymer chains themselves apart from literature on submonolayer studies of VDP [16] that reported the existence of three distinct growth regimes: initiation (I), chain propagation (P ), and saturation regime (S) and the recent experimental work on island nucleation during VDP [20] that indicates a new type of surface growth governed by reaction-limited aggregation in the films grown by VDP.…”
mentioning
confidence: 99%